2004
DOI: 10.1149/1.1723499
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Au(111)-Like Polycrystalline Gold Electrodes and Their Applications to Oxygen Reduction

Abstract: In the present study, we introduced a simple method for the fabrication of Au͑111͒-like polycrystalline Au electrodes via the formation of a submonolayer ͓i.e., sub-self-assembled monolayer ͑sub-SAM͒/Au͔ of a thiol compound ͓e.g., cysteine ͑CYST͒, mercaptoacetic acid, or cystamine͔. The oxygen reduction reaction ͑ORR͒ in alkaline medium (O 2 -saturated 0.5 M KOH͒ performed at these sub-SAM/Au electrodes proceeds via a two-electron quasi-reversible pathway irrespective of the charge of the terminal group of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
91
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 37 publications
9
91
0
Order By: Relevance
“…Recently Ohsaka et al [16,19,20] analyzed the reductive desorption behavior of cysteine, 4-mercaptobenzoic acid and mercaptoacetic acid from poly-Au electrodes by comparing the position of the desorption peaks to the peak position for desorption from single crystalline gold substrates. The multiple waves observed at poly-Au were correlated with the single reductive desorption waves of the low index surfaces, i.e., (111), (100) and (110) of the single crystalline gold substrates [16,19]. The stability of the adsorbates differs substantially depending on the surface crystallographic orientation, in the order (111) < (100) < (110).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Ohsaka et al [16,19,20] analyzed the reductive desorption behavior of cysteine, 4-mercaptobenzoic acid and mercaptoacetic acid from poly-Au electrodes by comparing the position of the desorption peaks to the peak position for desorption from single crystalline gold substrates. The multiple waves observed at poly-Au were correlated with the single reductive desorption waves of the low index surfaces, i.e., (111), (100) and (110) of the single crystalline gold substrates [16,19]. The stability of the adsorbates differs substantially depending on the surface crystallographic orientation, in the order (111) < (100) < (110).…”
Section: Introductionmentioning
confidence: 99%
“…This is an exception, since reductive desorption from single crystal surfaces normally proceed in a single reduction step, resulting in a single desorption peak. A single peak is also observed for the desorption of MPA from each of the single crystal planes Au(111) [14,16,19], Au(110) and Au(100) [16,19]. It is not very likely that the change from a single crystalline gold substrates to poly-Au could would lead to a change in the fundamental reduction mechanism, though it can not totally ruled out.…”
Section: Introductionmentioning
confidence: 99%
“…Selective desorption of the SAMs was achieved in order to improve the performance/control of the porosity of the thiolated layer that guarantees a partially unblocked electrode surface with a high number of bare exposed domains on the electrode surface [25]. Reductive partial desorption of MUA SAM from the microelectrode surface was carried out by LSV (Figure 3, Inset).…”
Section: Partial Reductive Desorption Of Sams On the Different Substrmentioning
confidence: 99%
“…A similar behavior was observed for other SAMs formed by short-chain thiolated molecules. For instance, it was previously reported that O 2 reduction was completely blocked at an intact threecarbon cysteine SAM-coated gold electrode [25]. However, this reaction was possible when cysteine was selectively desorbed from the electrode surface and a SAM submonolayer was thus obtained.…”
Section: à2mentioning
confidence: 99%
See 1 more Smart Citation